2022
DOI: 10.3390/molecules27020456
|View full text |Cite
|
Sign up to set email alerts
|

Process Parameters Optimization, Characterization, and Application of KOH-Activated Norway Spruce Bark Graphitic Biochars for Efficient Azo Dye Adsorption

Abstract: In this work, Norway spruce bark was used as a precursor to prepare activated biochars (BCs) via chemical activation with potassium hydroxide (KOH) as a chemical activator. A Box–Behnken design (BBD) was conducted to evaluate and identify the optimal conditions to reach high specific surface area and high mass yield of BC samples. The studied BC preparation parameters and their levels were as follows: pyrolysis temperature (700, 800, and 900 °C), holding time (1, 2, and 3 h), and ratio of the biomass: chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 50 publications
(160 reference statements)
1
19
0
Order By: Relevance
“…The overall percentage removal was calculated considering the area under the curve of the UV–vis (190–800 nm) spectra of the two synthetic effluents before and after the treatment ,,, (see Figure ). The results exhibited satisfactory percentage removals for both effluents: Effluent A’s and Effluent B’s percentage removal was 40.0 and 48.0%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The overall percentage removal was calculated considering the area under the curve of the UV–vis (190–800 nm) spectra of the two synthetic effluents before and after the treatment ,,, (see Figure ). The results exhibited satisfactory percentage removals for both effluents: Effluent A’s and Effluent B’s percentage removal was 40.0 and 48.0%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphoric acid and Zinc chloride are two of the most often used activating agents in chemical activation, aside from NaOH and KOH [20,21]. Therefore, many research studies have been published during the last couple of years investigating the use of biochar to adsorb dyes and in wastewater treatment processes [22][23][24][25][26][27][28][29][30][31][32][33]. CV and/or MB dyes were adsorbed from aqueous media by various types of biochar such as eucalyptus camaldulensis biochar (Ec-bio) [22], porous biochar [23], mesoporous seaweed biochar [24], castor biomass-based biochar [25], adsorbents from orange peel residues [26], biochar at different carbonization times [28], date palm fronds biochars [31], and rice husk-mediated magnetic biochar (RH-MBC) [33].…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 33 , 38 Indeed, carbon-based materials are expected to be more hydrophobic than hydrophilic. 13 , 38 , 39 However, Guy et al 40 prepared biochars by alkaline activation (KOH) using Norway spruce bark as a precursor and found that most biochars were hydrophilic. This contradiction could be related to the differences in the precursor; bark is more homogeneous with abundant oxygen and hydrogen groups, while paper and pulp sludge has been subjected to several extraction methods that may remove many of these hydrophilic groups, which in turn might impact the final biochar characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic–hydrophilic behavior of the 15 biochar samples was evaluated, and n -heptane:water adsorption ratios are exhibited in Figure . All biochars had a ratio >1, meaning a higher affinity for n -heptane, meaning that the surfaces were predominantly hydrophobic. ,, Indeed, carbon-based materials are expected to be more hydrophobic than hydrophilic. ,, However, Guy et al prepared biochars by alkaline activation (KOH) using Norway spruce bark as a precursor and found that most biochars were hydrophilic. This contradiction could be related to the differences in the precursor; bark is more homogeneous with abundant oxygen and hydrogen groups, while paper and pulp sludge has been subjected to several extraction methods that may remove many of these hydrophilic groups, which in turn might impact the final biochar characteristics.…”
Section: Resultsmentioning
confidence: 99%